AtomDB: A Python Library and Database for Atomic and Promolecular Properties - Sánchez Díaz, Gabriela; Richer, Michelle; Martínez González, Marco; van Zyl, Maximilian; Pujal, Leila; Tehrani, Alireza; Bianchi, Julianna; Chuiko, Valerii; Erhard, Jannis; Meng, Fanwang; Ayers, Paul W; Heidar-Zadeh, Farnaz (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2025)
AtomDB is a free and open-source Python library for accessing and manipulating neutral and charged atomic species and their promolecular properties. It serves as a computational toolset, operating on an accompanying "extended periodic table" database, with experimental and computational data covering atomic species with a wide range of charges and multiplicities. AtomDB includes facilities for computing promolecules: local promolecular properties, constructed from the corresponding atomic densities, and scalar promolecular properties, computed from the corresponding scalar atomic properties, both taking into account whether properties are extensive or intensive. AtomDB is designed to be easy to use, extend, and maintain: it follows best practices for modern software development, including comprehensive documentation, extensive testing, continuous integration/delivery protocols, and package management. This article is the official release note for the AtomDB library.